2022
DOI: 10.1002/ecy.3699
|View full text |Cite
|
Sign up to set email alerts
|

Smaller species but larger stages: Warming effects on inter‐ and intraspecific community size structure

Abstract: Global warming can alter size distributions of animal communities, but the contribution of size shifts within versus between species to such changes remains unknown. In particular, it is unclear if expected body size shrinkage in response to warming, observed at the interspecific level, can be used to infer similar size shifts within species. In this study, we compare warming effects on interspecific (relative species abundance) versus intraspecific (relative stage abundance) size structure of competing consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 90 publications
(141 reference statements)
2
6
0
Order By: Relevance
“…Warming leads to a shift in species composition, favouring a lower trophic position in the multispecies IGP community in Paper IV and an accumulation of biomass in the smaller adult stage in the consumer-resource community in Paper III. This supports the prediction of smaller species and larger stages when accounting for size dependent effects of warming (Uszko et al 2022). Considering theoretical expectations of reduced energetic efficiency from warming in higher trophic levels (Vucic-Pestic et al 2011;Fussmann et al 2014), there is an important difference in how temperature shapes the energetic efficiency within species preceding the extinction in the two models.…”
Section: Warming Induced Changes In Population and Community Structuresupporting
confidence: 80%
See 3 more Smart Citations
“…Warming leads to a shift in species composition, favouring a lower trophic position in the multispecies IGP community in Paper IV and an accumulation of biomass in the smaller adult stage in the consumer-resource community in Paper III. This supports the prediction of smaller species and larger stages when accounting for size dependent effects of warming (Uszko et al 2022). Considering theoretical expectations of reduced energetic efficiency from warming in higher trophic levels (Vucic-Pestic et al 2011;Fussmann et al 2014), there is an important difference in how temperature shapes the energetic efficiency within species preceding the extinction in the two models.…”
Section: Warming Induced Changes In Population and Community Structuresupporting
confidence: 80%
“…As body size determines the energy demand and temperature sensitivity of energetic efficiency, size differences between trophic levels can determine how system carrying capacity (a system's ability to hold standing biomass based on environmental conditions) respond to warming (Arim et al 2007;Binzer et al 2012). Because of responses in primary production, carrying capacity should be unimodal over the full biological temperature range, and thus decrease in the higher temperature range (Lemoine 2019;Uszko et al 2022). Consequently, food web responses to warming are predicted to depend on the temperature range examined, how warming changes energetic efficiency across trophic levels, on effects on primary production but also on biomass loss via mortality affecting competition for resources (Vasseur & McCann 2005;Binzer et al 2012).…”
Section: Temperature Body Size and Community Ecologymentioning
confidence: 99%
See 2 more Smart Citations
“…However, there is still a lack of fully targeted experimental examination on warming‐induced changes in interspecific size structures of zooplankton communities with high species and taxon diversity. Recently, a study reviewed 123 experimental or observational studies on this (Uszko et al, 2022), and a majority of them (91) observed a shift from larger to smaller species, and only 14 reported the opposite effect. Besides, that study reproduced the expected warming effect at the community composition level by modeling.…”
Section: Discussionmentioning
confidence: 99%